Winning against MNCs in emerging markets: strategies of domestic firms in India - Arora, Sanchit (2019)
The study addresses the less-explored issue of how domestic companies in the emerging markets counter the challenges from the multinational corporations (MNCs) on their own turf. Prior literature on the topic widely adopts a pessimist approach towards domestic firms and argues that global companies enjoy significant advantages over domestic firms in head-to-head competition. This study contradicts these arguments by developing in-depth case studies and analysing competitive strategies of the domestic firms in India based on triangulation of primary and secondary data.